Genetic characteristics of two of human rhinovirus A49 detected in Ningxia Hui Autonomous Region in 2021: a whole-genome analysis - Yanyan SU; Yanxue LI; Xinning WANG; Jianxin PEI; Zhonglan WU; Xueping MA; Yinhao ZHANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze genetic characteristics and variation in whole-genome sequence of two human rhinovirus (HRV) A49 strains detected in Yinchuan city, Ningxia Hui Autonomous Region in 2021. MethodsThe study involved two HRV nucleic acid positive nasopharyngeal swab samples collected during 2021 from two child respiratory infections at two sentinel hospitals in Yinchuan city, Ningxia Hui Autonomous Region. Whole-genome sequencing was performed on the two HRV specimens. The reference sequence was downloaded from GenBank database; Mafft was used for sequence comparison; MEGA11 was used to construct phylogenetic tree; and Beast1.10.4 was used to construct Bayesian phylogenetic tree. Nucleotide (amino acid) homology and variation were analyzed with DNAStar software. ResultsThe whole genome sequence was obtained from the two detected HRV strains belonged to HRV-A49 serotype. The nucleotide (amino acid) homology between the two strains was 96.9% (99.5%). One of the two strains named 719/CHN/YinChuan/2021-09 (abbreviated as 719) was isolated from a 2-year-old girl with single HRV infection. For the 719 strain, the total sequence length is 7103 bp; the CG content is 38.97%; and is of closest genetic relation to the OL961540 strain detected during 2021 in American, with the nucleotide homology of 99.1% and the highest amino acid homology 99.8% to strains of OL133734, OK254862, and MZ629143. The other of the two strains named 847/CHN/YinChuan/2021-10 (abbreviated as 847) was isolated from a 3-year-old girl having HRV co-infection with parainfluenza virus type III. For the 847 strain, the total sequence length is 7038 bp; the CG content is 39.61%; and is of closest genetic relation to the MW587079 strain detected during 2017 in China, with the nucleotide (amino acid) homology of 98.2% (99.5%). Compared with those of reference strains, 69 and 66 amino acid mutation sites were detected in 719 and 847 strains according to amino acid variation analysis. In comparison to strains having the highest amino acid homology, there were 5 site mutations in 719 strain as opposed to OL133734, OK254862 and MZ629143 strains and 6 site mutations in 847 strain in relation to OL133734, OK254862, MZ629143 and MW587079 strains. ConclusionThe two HRV strains detected in Yinchuan city during 2021 belong to HRV A49 serotype and there is significant genetic variation in VP1, 3C and 3D protein coding region.